Differentiation of Islet Progenitors Regulated by Nicotinamide into Transcriptome‐Verified β Cells That Ameliorate Diabetes. (23rd February 2017) - Jiang, Fang‐Xu; Li, Kevin; Archer, Michael; Mehta, Munish; Jamieson, Emma; Charles, Adrian; Dickinson, Jan E.; Matsumoto, Masahito; Morahan, Grant
Abstract: Developmental stage‐specific differentiation of stem or progenitor cells into safe and functional cells is of fundamental importance in regenerative medicine, including β‐cell replacement. However, the differentiation of islet progenitor cells (IPCs) into insulin‐secreting β cells remains elusive. Here, we report that the multifunctional molecule nicotinamide (NIC) is a specific differentiation regulator of mouse IPCs. The differentiated cells regulated by NIC exhibited many characteristics of adult β cells, including ameliorating preclinical diabetes and a highly comparable transcriptome profile. Gene set enrichment analysis showed that during differentiation, numerous IPC transcription factor genes, including Ngn3, Pax4, Fev, and Mycl1, were all down regulated. Pharmacological, biochemical, and gene knockdown analyses collectively demonstrated that NIC regulated the differentiation via inhibiting Sirt1 (silent information regulator transcript 1). Finally, NIC also regulates human IPC differentiation. Thus, our study advances islet developmental biology and impacts on translational research and regenerative therapies to diabetes and other diseases. Stem Cells 2017;35:1341–1354 Abstract : Molecular mechanisms underlying nicotinamide (NIC)‐regulated differentiation of insulin‐secreting β cells. NIC is a non‐competitive physiological inhibitor of Sirt1 (silent information regulator transcript 1), a member of class III histone deacetylases (HDACs) dependent on NIC adenine dinucleotide (NAD). NIC inhibits Sirt1 in islet neurogenin 3 (Ngn3)‐expressing progenitor cells and promotes the differentiation of insulin‐secreting β cells. In contrast, isonicotinamide and resveratrol (Resv) activate Sirt1 thus inhibit the differentiation. Treatment with pyruvate could elevate the cytoplasmic NAD concentration and increase Sirt1 activity. The promotion of islet progenitor differentiation by Sirt1 shRNA confirms the negative role of Sirt1.